Male hormones activate EphA2 to facilitate Kaposi's sarcoma-associated herpesvirus infection: Implications for gender disparity in Kaposi's sarcoma. - Xing Wang; Zhe Zou; Zhaohui Deng; Deguang Liang; Xin Zhou; Rui Sun; Ke Lan (PLoS Pathogens, 2017)
There is increasing consensus that males are more vulnerable than females to infection by several pathogens. However, the underlying mechanism needs further investigation. Here, it was showed that knockdown of androgen receptor (AR) expression or pre-treatment with 5α-dihydrotestosterone, the AR agonist, led to a considerably dysregulated Kaposi's sarcoma-associated herpesvirus (KSHV) infection. In endothelial cells, membrane-localized AR promoted the endocytosis and nuclear trafficking of KSHV. The AR interacted with ephrin receptor A2 (EphA2) and increased its phosphorylation at residue Ser897, which was specifically upregulated upon KSHV infection. This phosphorylation resulted from the AR-mediated recruitment of Src, which resulted in the activation of p90 ribosomal S6 kinase 1 (RSK1), which directly phosphorylates EphA2 at Ser897. Finally, the EphA2-mediated entry of KSHV was abolished in a Ser897Asn EphA2 mutant. Taken together, membrane-localized AR was identified as a KSHV entry factor that cooperatively activates Src/RSK1/EphA2 signaling, which subsequently promotes KSHV infection of both endothelial and epithelial cells.